The role of microparticles in pathomechanisms of diabetic retinopathy – analysis of intercellular communication mechanisms in endothelial aging. Case control study in patients with metabolic syndrome, diabetes type 1 and type 2 - Stępień, Ewa; Szuścik, Iwona; Tokarz, Aleksandra; Enguita, Francisco J.; Solnica, Bogdan; Żurakowski, Aleksander; Małecki, Maciej (Journal of Medical Science, 2014)
The project is proposed to explain the role of specific circulating microparticles (MPs) as conveyors in trafficking bio-active molecules in type 1 (T1DM) and type 2 (T2DM) diabetic patients with risk of diabetic retinopathy (DR) and in patients with metabolic syndrome (MS). The possible role of miRNAs as modulators of these processes (in switching on/off mechanism on the molecular level) is proposed. An increased number of MPs with respect to glucose concentrations and levels of proangiogenic factors in vivo (patients’ plasma) is expected. The relationship between age of patents and MP content (cell membrane glycoproteins, phosphatidylserine or miRNA profile) is possible. MPs will be obtained from T1DM (n = 30) T2DM (n = 30), MS (n = 30) and controls (n = 30). Retinopathy in diabetic patients will be assessed by imaging method. Biological profile of MPs will be assessed in vitro by means of flow cytometry, molecular biology methods and cell proliferation assays.